A prospective study of the prevalence of corneal surface disease in dogs receiving prophylactic topical lubrication under general anesthesia. (28th March 2015) - Dawson, Charlotte; Sanchez, Rick F.
Abstract: Objective: To identify the prevalence of corneal ulceration in dogs receiving prophylactic gel lubrication under general anesthesia (GA). Materials and methods: An ophthalmic examination was performed before premedication and 24 h after GA in 100 dogs (199 eyes) undergoing nonophthalmic procedures. Individuals with known pre‐existing ocular surface conditions were excluded. An ocular lubricating gel containing carmellose sodium was applied by the anesthetist at induction and every 2–4 h until extubation. Logistic regression analysis was used to calculate risk factors for ulcerative disease, including signalment, length of GA, patient position, procedure performed, pre‐, and post‐GA ophthalmic examination findings and admitting service. A Wilcoxon rank sum test compared pre‐ and post‐GA Schirmer tear test‐1 (STT‐1) values. Results: One dog (0.5% of total eyes) developed fluorescein stain uptake consistent with superficial corneal ulceration that resolved within 48 h with supportive treatment. Twenty‐five (18.6% of total eyes) developed a faint, patchy corneal uptake of stain in the axial cornea that was consistent with epithelial erosion. All erosions resolved with lubrication 24 h later. The decrease in STT‐1 readings at 24 h post‐GA was statistically significant from those pre‐GA ( P  < 0.001). No significant risk factors for corneal erosion/ulceration were identified. Conclusions: The results of this study show that a basic protocol of prophylactic lubrication during GA was associated with a low prevalence of corneal ulceration but a higher prevalence of epithelial erosion. In addition, the study supports the need for post‐GA corneal examination.